2018
DOI: 10.3389/fmicb.2018.00163
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Most Prevalent Spa Types among Clinical Isolates of Methicillin-Resistant and -Susceptible Staphylococcus aureus around the World: A Review

Abstract: Background: Staphylococcus aureus, a leading cause of community-acquired and nosocomial infections, remains a major health problem worldwide. Molecular typing methods, such as spa typing, are vital for the control and, when typing can be made more timely, prevention of S. aureus spread around healthcare settings. The current study aims to review the literature to report the most common clinical spa types around the world, which is important for epidemiological surveys and nosocomial infection control policies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
112
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 266 publications
13
112
2
1
Order By: Relevance
“…In our study the ten different spa types detected had variable biofilm formation abilities. In agreement with data which indicated t790 as the most common spa type in Iran [33], the present research reports a prevalence of this spa type in 25.3% of isolates. We also found that 790 isolates had a greater propensity to form biofilm compared to other spa types.…”
Section: Discussionsupporting
confidence: 92%
“…In our study the ten different spa types detected had variable biofilm formation abilities. In agreement with data which indicated t790 as the most common spa type in Iran [33], the present research reports a prevalence of this spa type in 25.3% of isolates. We also found that 790 isolates had a greater propensity to form biofilm compared to other spa types.…”
Section: Discussionsupporting
confidence: 92%
“…MSSA spa and STs were diverse, as noted in previous studies. [25] However, ST188 and ST5 were the most common MSSA clones, consistent with previous reports of community-associated MSSA among adults and children in China. [26] ST188 virulence has been in part attributed to epithelial cell adhesion and biofilm formation, properties which could facilitate nasal colonization.…”
Section: Discussionsupporting
confidence: 89%
“…Staphylococcus protein A ( spa ) is implicated in virulence and typing of this gene by identifying the specific repeats in its variable repeat region has historically been used to distinguish between circulating variants of S. aureus during an outbreak. Among our isolates, the two most common spa types are t002 (25 isolates) and t008 (10 isolates) (Table 1), both of which are common types in the United States [41]. JE2 was confirmed as spa type t008 in our analysis.…”
Section: Resultsmentioning
confidence: 72%